Environmental, Social, Governance Disclosure, Leverage and Firm Value of Manufacturing Companies Listed on the Indonesian Sharia Stock Index - Fadmaulida, Nilam; Putra, Rosyid Nur Anggara (Journal of Accounting Inquiry, 2024)
Purpose: This research aims to analyze the influence of environmental, social, governance disclosure and leverage on firm value in manufacturing companies listed on the Indonesian Sharia Stock Index (ISSI) for 2016-2021. Methodology: The sample in this research is manufacturing companies that meet specific criteria which were selected using a purposive sampling technique with a total research sample of 129 observation data. The data analysis technique used is multiple regression analysis which is processed using e-views12. Findings: The research results show that environmental disclosure has a negative effect on company value, social disclosure has a positive effect on company value, governance disclosure and leverage have no effect on company value. These results support signal theory and legitimacy theory, where a company's disclosure of certain information can provide a signal to show that the company has good value. Companies influence public perception by carrying out their business in accordance with applicable regulations in order to gain public trust which has implications for increasing company value. Novelty: This research uses manufacturing companies listed on the indonesian sharia stock index from 2016 – 2021 and add leverage variable.